The political economy of regulation in the Philippine power sector - Baylon, Minerva S. (Philippine Journal of Public Administration, 2007)
This study presents some of the major issues and problems challenging the institution of effective regulatory reforms in developing countries discussed in the literature and how the Philippine experience in formulating a regulatory policy like the Electric Power Industry Reform Act (EPIRA) illustrates these issues. It shows how the politics of regulation in a developing country like the Philippines can frustrate efforts to design and put in place regulatory policies, systems and institutions to complement and ensure the success of economic reforms. It lends support to conceptual and empirical researches advocating the importance of taking into account the political and administrative, socioeconomic and cultural contexts in designing a regulatory policy and provides some explanation as to why reform policies may or may not succeed. Major lessons learned from the experience in formulating the EPIRA, and some policy recommendations aimed at improving the present system and process of policymaking in order to minimise opportunities for political capture are offered. Significant reform initiatives and developments concurrent with these recommendations and areas needing further research are likewise described.